(untitled) (Світ фінансів, 2017)
Желюк Т. Л. Конкурентоспроможність як ефективна форма функціонування національної економіки: підходи до оцінювання в системі глобальних координатм. Систематизовано наукові концепції конкурентоспроможності національної економіки. Визначено особливості формування конкурентних переваг сучасної економіки. Розкрито організаційно-методичні підходи до оцінювання конкурентоспроможності національної економіки. Проаналізовано структуру та диверсифікацію індексу глобальної конкурентоспроможності з визначенням тенденцій та перспектив для економіки України. Zhelyuk T. Competitiveness as an effective form of functioning of national economy: approaches to evaluation in the system of global co-ordinates. Scientific concepts of competitiveness of national economy are systematized. The peculiarities of competitive edges forming of modern economy are defined. Organizational and methodical approaches to the evaluation of national economy competitiveness are exposed. The structure and diversification of global competitiveness index with determination of tendencies and prospects for the economy of Ukraine are analysed.